International normalised ratio monitoring in the community populations of the Auckland and Northland regions of New Zealand: time in therapeutic range and frequency of testing. Issue 12 (5th December 2018) - McAuliffe, Gary N.; De Silva, Fransisca; Upton, Arlo; Chan, George
Abstract: Background: Warfarin remains a commonly used anticoagulant for the treatment and prevention of thrombosis. To balance the risks and benefits of therapy, monitoring of the international normalised ratio (INR) is necessary. Patients derive most benefit from warfarin when they spend ≥65% of time in the therapeutic range (INR 2–3). We performed an analysis of INR monitoring for the Auckland and Northland regions of New Zealand in order to estimate anticoagulation control and appropriateness of testing at the population level. Methods: INR test results and patient demographics (age and sex) were extracted from the laboratory information system of Labtests and Northland Pathology Laboratories for the period of 1 January 2016 to 27 July 2016. Results: We included 126 184 INR results from 10 922 patients. The median age of patients represented was 74 years and 57% were male. The overall mean time in therapeutic range was 63%, with a mean interval between INR tests of 14 days. Conclusion: Our results indicate that anticoagulant control in our communities could be improved, and that inappropriately frequent INR testing should be redressed. Appropriate interventions could lead to net clinical benefits and reduce resource misallocation.